2006
DOI: 10.1645/ge-717r.1
|View full text |Cite
|
Sign up to set email alerts
|

Louse-Borne Bacterial Pathogens in Lice (Phthiraptera) of Rodents and Cattle From Egypt

Abstract: We collected 1,023 lice, representing 5 species, from rats and domestic cattle throughout 13 governorates in Egypt and tested these lice for Anaplasma marginale, Bartonella spp., Brucella spp., Borrelia recurrentis, Coxiella burnetii, Francisella tularensis, and Rickettsia spp. by PCR amplification and sequencing. Five different louse-borne bacterial agents were detected in lice from rodents or cattle, including "Bartonella rattimassiliensis", "B. phoceensis", and Bartonella sp. near Bartonella tribocorum, Cox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…In addition, cattle and feline associated Bartonella DNA were detected in the blood of dairy cattle from seven Israeli dairy farms. Previous studies that screened Bartonella DNA on Haematopinus species lice collected from pigs and cattle reported negative results (33,34). Therefore, to the best of our knowledge, this is the first report of Bartonella detection in this louse genus.…”
Section: Discussionmentioning
confidence: 65%
“…In addition, cattle and feline associated Bartonella DNA were detected in the blood of dairy cattle from seven Israeli dairy farms. Previous studies that screened Bartonella DNA on Haematopinus species lice collected from pigs and cattle reported negative results (33,34). Therefore, to the best of our knowledge, this is the first report of Bartonella detection in this louse genus.…”
Section: Discussionmentioning
confidence: 65%
“…Reeves and others 26 hypothesized that B. phoceensis might be associated with or transmitted by Hoplopleura pacifica lice but not P. spinulosa because B. phoceensis was detected only in H. pacifica collected from a B. rattimassiliensis -infected rat. In the present study, B. phoceensis was detected in 8 Polyplax spp.…”
Section: Discussionmentioning
confidence: 99%
“…Ctenophthalmus nobilis , a rodent flea, has been demonstrated as a competent vector for transmission of B. grahamii and B. taylorii in rodents. 24 However, Bartonella DNA has also been detected in lice, 25,26 fleas, 25 Mesostigmatid mites, 27 and ticks 27 collected on small mammals; these ectoparasites are considered potential vectors for various Bartonella species. The role of these potential vectors in Bartonella transmission among rodent hosts needs to be confirmed.…”
mentioning
confidence: 99%
“…Infection with this Bartonella variant did not affect the metabolic rate, blood consumption, life span, fertility, or fecundity of female fleas, nor the developmental time, the life span, or sex ratio of their offspring fleas (Morick et al 2013b). Interestingly, bartonellae DNA has been detected in other rodent ectoparasites, including ticks, mites, and lice (Durden et al 2004, Kim et al 2005, Reeves et al 2006. A recent study has demonstrated the competency of Ixodes ricinus ticks to transmit the rodent-associated B. birtlesii (Reis et al 2011).…”
Section: Figmentioning
confidence: 98%